Rolling Back Malaria : the World Bank Global Strategy & Booster Program. (World Bank e-Library., 2005)
"Malaria afflicts millions in low- and middle-income countries. For centuries, it has impaired economic growth, child development, learning, health, and productivity on a large scale. In 1998 the Bank cofounded, with WHO, UNICEF, and UNDP, the global Roll Back Malaria Partnership to coordinate and enhance the global fight against malaria. There has been some success, but the pace of work was slower than desired and the scale was less than expected. The world now faces additional challenges, not the least of which is the emergence of drug-resistant forms of malaria. This new Global Strategy increases efforts to control malaria. It lays the basis for a Booster Program for Malaria Control using country-led programs and partnerships with community service organizations, specialized agencies, and financiers of malaria control at all levels. The new Global Strategic Plan of the Roll Back Malaria Partnership combines measures to increase coverage of malaria-specific interventions with effective service delivery, broader health-system development, and capacity building across multiple sectors."--Publisher's website